Aaker Customer Implementation through Brand Equity in RTV Innovation Marketing Programs - Yandri, Firman Okta; Marsasi, Endy Gunanto (Fakultas Ekonomi Universitas Samudra, 2024)
This research aims to analyze the problems that exist in a company in the entertainment sector, namely regional television operating in Riau Melayu, mainly the marketing used. The research was conducted using descriptive qualitative research methods using secondary and primary data obtained through interview, observation, and documentation collection methods. This research obtained results from weaknesses that occurred through SWOT analysis, so an evaluation was carried out to form brand equity in the marketing media that had previously used brand equity. The theory used in this research is the Aaker Brand Equity Theory, where Riau TV is expected to be able to manage the company's existing marketing media through existing social media. This program will form a good perception and experience for its loyal viewers so that Riau TV has a good image in society.